Peningkatan Kesadaran dan Pemahaman Ekonomi Syariah Melalui Program Penyuluhan Komprehensif - Warto, Warto; Nurzansyah, Muhammad; Putri Rahmawan, Nabila; Tegar Firmansyah, Marselino (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
The purpose of this counseling is to increase public awareness and literacy about the principles of sharia economics and encourage the adoption of sharia financial products. The activity was carried out in Bogor Regency with 120 participants. This counseling uses an interactive and comprehensive discussion approach in each session. The material is given in three phases: Introduction, Implementation, and Evaluation. The results showed that 96 people stated they understood the principles of Sharia economics and were ready to implement financial management based on Islamic principles.